Pendidikan dan Teknologi: Optimalkan Pembelajaran di Era Digital - Bahani1, Fadli Nur; Kholid, Muhammad Haidar (Indo-MathEdu Intellectuals Journal, 2024)
The digital era brings significant changes in various aspects of life, including education. This article explores the application of technology in education in the digital era, outlining the positive impacts, challenges faced, and strategic steps to optimize the benefits of technology in learning. The research method used is descriptive qualitative method through literature study from various sources of relevant journals and articles. The results show that technology improves accessibility, interactivity and personalization of learning. However, the access gap and curriculum adaptation are still the main challenges. Proposed solutions include subsidizing technology and internet devices, curriculum adaptation and professional training for teachers. With these measures, technology can be optimally utilized to improve the quality of education and provide a better learning experience for all students